PENYULUH PAJAK: PENERAPAN CUSTOMER BASED ORIENTED SERVICES DI DIREKTORAT JENDERAL PAJAK - Agustinus Imam Saputra (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2022)
This study attempts to elaborate on the strategy of service quality and customer satisfaction at Nordstrom as a reflection of the leading private sector. Furthermore, the study wants to bring and adapt Nordstrom's achievements to the public sector, especially for the Indonesian tax authority, Directorate General of Taxes (DJP). Moreover, in 2020, a regulation on tax counselor personnel at the DJP has been issued. Since customer satisfaction increases awareness of fulfilling tax obligations voluntarily, this study is critical to empower tax counselor personnel. It uses descriptive qualitative research methods. Research data were obtained from document and regulation review. Essential lessons from a leading private company customer services strategy are the right people, empowered employee, dan motivating employee. Furthermore, it is necessary to measure the success of customer based oriented services at DJP. The organisation should refer to the success story of Nordstrom, as best practice in satisfying customers. This research can be a trigger of further research in all areas of the public sector.